Clinically significant depressive symptoms and sexual behaviour among men who have sex with men - Miltz, Ada R.; Rodger, Alison J.; Sewell, Janey; Speakman, Andrew; Phillips, Andrew N.; Sherr, Lorraine; Gilson, Richard J.; Asboe, David; Nwokolo, Nneka C.; Clarke, Amanda; Gompels, Mark M.; Allan, Sris; et al. (BJPsych open, 2017)
The relationship between depression and sexual behaviour among men who have sex with men (MSM) is poorly understood. To investigate prevalence and correlates of depressive symptoms (Patient Health Questionnaire-9 score ≥10) and the relationship between depressive symptoms and sexual behaviour among MSM reporting recent sex. The Attitudes to and Understanding of Risk of Acquisition of HIV (AURAH) is a cross-sectional study of UK genitourinary medicine clinic attendees without diagnosed HIV (2013-2014). Among 1340 MSM, depressive symptoms (12.4%) were strongly associated with socioeconomic disadvantage and lower supportive network. Adjusted for key sociodemographic factors, depressive symptoms were associated with measures of condomless sex partners in the past 3 months (≥2 (prevalence ratio (PR) 1.42, 95% CI 1.17-1.74; =0.001), unknown or HIV-positive status (PR 1.43, 95% CI 1.20-1.71; <0.001)), sexually transmitted infection (STI) diagnosis (PR 1.46, 95% CI 1.19-1.79; <0.001) and post-exposure prophylaxis use in the past year (PR 1.83, 95% CI 1.33-2.50; <0.001). Management of mental health may play a role in HIV and STI prevention. A.N.P. has received payments for presentations made at meetings sponsored by Gilead in spring 2015. N.C.N. has received support for attendance at conferences, speaker fees and payments for attendance at advisory boards from Gilead Sciences, Viiv Healthcare, Janssen Pharmaceuticals and Bristol-Myers Squibb and a research grant from Gilead Sciences. D.A. served on the advisory board for Gilead in January 2016. M.M.G. has had sponsorship to attend conferences by Bristol-Myers Squibb, been on the BioCryst advisory board and run trials for Merck, Gilead, SSAT, BioCryst and Novartis. © The Royal College of Psychiatrists 2017. This is an open access article distributed under the terms of the Creative Commons Non-Commercial, No Derivatives (CC BY-NC-ND) license.